C1q/TNF-related protein-9 ameliorates hypoxia-induced pulmonary hypertension by regulating secretion of endothelin-1 and nitric oxide mediated by AMPK in rats - Qiaoyan Jin (Nature Portfolio, 2021)
Abstract Injury/dysfunction of the endothelium of pulmonary arteries contributes to hypoxia-induced pulmonary hypertension (HPH). We investigated whether C1q/tumor necrosis factor-related protein-9 (CTRP9), a newly identified cardiovascular agent, has protective roles in the development of HPH. HPH was induced in adult male rats by chronic hypobaric hypoxia. CTRP9 overexpression by adeno-associated virus (AAV)-CTRP9 transfection attenuated the increases in right ventricular systolic pressure, right ventricular hypertrophy index, and pulmonary arterial remodeling of rats under hypoxia. Importantly, CTRP9 overexpression improved endothelium-dependent vasodilation in pulmonary arterioles in HPH rats. CTRP9 overexpression enhanced expression of phosphorylated 5′-adenosine monophosphate-activated protein kinase (p-AMPK) and phosphorylated endothelial nitric oxide synthase (p-eNOS), and reduced phosphorylated extracellular signal-regulated protein kinase (p-ERK1/2) expression in pulmonary microvascular endothelial cells (PMVECs) of HPH rats. In cultured PMVECs, CTRP9 not only preserved the decrease of AMPK and eNOS phosphorylation level and nitric oxide (NO) production induced by hypoxia, but also blocked the increase in hypoxia-induced ERK1/2 phosphorylation level and endothelin (ET)-1 production. Furthermore, the effects of CTRP9 were interrupted by inhibitors or knockdown of AMPK. CTRP9 enhances NO production and reduces ET-1 production by regulating AMPK activation. CTRP9 could be a target for HPH.